Transmissão de futebol por streaming: a reconfiguração das territorialidades do RS no caso FGF TV - Dias, Yuri Cougo (Universidade do Vale do Rio dos Sinos, 2023)
This work aims to verify how the streaming platform, FGF TV, reconfigures the territorialities of gaucho football and what discourses the communicating subjects generate in these media processes. To achieve these results, we contextualize what kind of visibility there is in these transmissions; the discourses adopted by professionals about the territorialities of each team; the interactivity of fans on the platform and the conditions for these media processes to take place. To obtain the results, a series of methods were used, with emphasis on transmethodology and theories of discourse analysis and intellectual craftsmanship, so that we could understand in more depth the effects that these transmissions generate in the gaucho territorialities. In a brief description of the final results, it verified the importance of FGF TV for the phenomenon of media democracy, of transmitting games of teams that did not have visibility in the traditional means of communication. Also, we came to understand that the teams represent not just a sport, but a series of cultural, social and economic matrices of the cities/regions in which they are located. That is, visibility transcends the sporting aspect, thus proving the civilizing role that is intrinsic to soccer.
Keywords: Transmissão de futebol; Streaming; FGF TV; Territorialidades; Futebol gaúcho; Football broadcast; Territorialities; Football gaucho; ACCNPQ::Ciências Sociais Aplicadas::Comunicação